Significant contribution of organically-bound Mg, Ca, and Fe to inorganic PM10 emission during the combustion of pulverized Victorian brown coal - Gao, Xiangpeng; Rahim, Usman; Chen, Xixia; Wu, Hongwei (Elsevier Ltd, 2014)
This study deployed water-washing and dilute acid washing of a Victorian brown coal to prepare a set of coal samples with simplified occurrence forms of inorganic species. The resulted water-washed coal contains dominantly organically-bound species (primarily Mg, Ca, and Fe) and discrete mineral particles whereas the acid-washed coal only consists of discrete mineral particles. The coal samples (i.e., the raw, the water-washed and the acid-washed coals) were combusted in a lab-scale drop-tube furnace in air at 1400 °C to produce inorganic particulate matter (PM) with aerodynamic diameter less than 10 µm (PM10). Benchmarking on yields, particle size distribution, and chemical properties of PM10 produced from the combustion of the three coals clearly demonstrates that majority of PM10, including PM with aerodynamic diameter less than 1 µm (PM1) and between 1 and 10 µm (PM1–10), is contributed by organically-bound elements (mainly Mg, Ca, and Fe) whereas there is only limited contribution from discrete mineral particles due to their low contents in the brown coal. The results also clearly show that the water-soluble salts (e.g., NaCl) mainly contribute to the emission of PM with aerodynamic diameter less than 0.1 µm (PM0.1).